Digitalization of Geo-Information Support for Natural Risks Management within Large Arctic Projects - Valery M. ABRAMOV; Nickolay N. POPOV; Igor A. SIKAREV; Ekaterina M. KORINETS; Tatiana M. TATARNIKOVA; Sergey V. LUKYANOV; Oleg I. SHEVCHUK; Oksana PETRIEVA; Yaroslav A. PETROV; Tatiana V. VEKSHINA (Communications of International Proceedings, 2021)
Considered digitalization development results for geo-information support to natural risks management in large arctic projects under conditions of climate change and Covid-19 within Industry 4.0 period. In studies, there are used methods of data bases constructing, web-technologies and virtual reality tools. Also, there are used Foresight technologies, theory of decision making under uncertainties and risk management. As digital tools, it is proposed to use digital online platforms, which integrate heterogeneous hardware and software resources with the use of web-technologies in distributed networks and wide application of cloud services. As study results, some examples of geo-information support are demonstrated. The presented research results have significant scientific novelty and can be useful for private investors, environmental public organizations of the civil sector and state environmental control bodies. While research, the platform https://www.researchgate.net/profile/Valery_Abramov2/ was used for data exchange and preliminary discussion.
Keywords: Arctic Projects; Natural Risks Management; Digitalization; Climate Change; Covid-19